Prevalence and Risk Factors of Functional Constipation According to the Rome Criteria in China: A Systematic Review and Meta-Analysis - Chen, Zhe; Peng, Yingying; Shi, Qingyang; Chen, Yongjie; Cao, Lujia; Jia, Jiannan; Liu, Chunxiang; Zhang, Junhua (Frontiers in Medicine, 2022)
Background Functional constipation (FC) is a common bowel disorder that prevails worldwide. In China, although a heterogeneous prevalence of constipation is expected, it is currently not demonstrated. In this study, we aimed to evaluate the prevalence and related risk factors of FC in the Chinese population, according to the Rome criteria. Methods We searched the PubMed, the Embase, the Cochrane Library, the Web of Science, the China National Knowledge Infrastructure (CNKI), the Wanfang data knowledge service platform, the VIP information resource integration service platform, and the Chinese Biomedical Literature Service System (SinoMed) databases from the inception of database to July 2021. Population-based cross-section studies that enrolled adults with FC, diagnosed by the Rome criteria, were deemed eligible. We summarized the overall prevalence and detected the subgroup effect per the Rome I, Rome II, Rome III, and Rome IV criteria. We used the generalized linear mixed model (GLMM) with a random-effect intercept to pool the prevalence and performed pairwise meta-analyses for prevalence comparisons by risk factors. Results We identified 3,213 records through our database search, and 39 studies from China, comprising 1,240,79 participants, met the eligibility criteria for our study. The pooled overall prevalence of FC using the Rome criteria was 8.5% in China. Heterogeneous prevalence was detected within the Rome criteria (Rome II: 10.6%, 95% CI: 7.2–15.4; Rome III: 6.5%, 95% CI: 3.4–12.0; Rome IV: 8.1%, 95% CI: 5.6–11.8). The prevalence increased between 1991 and 2020 (from 5.5% with 95% CI: 3.6–8.2 between 1991 and 2000 to 10.9% with 95% CI: 5.5–20.4 between 2011 and 2020). Higher prevalence was found in women [odds ratio (OR) = 1.53, 95% CI: 1.31–1.78] and the elderly (≥70 years vs. ≤ 29 years: OR = 3.38, 95% CI: 2.16–5.30) than in men and the younger population. A high-fiber diet was associated with lower prevalence (OR = 0.33, 95% CI: 0.15–0.75), whereas irregular bowel habit and inactivity were associated with higher prevalence (OR = 3.64, 95% CI: 2.64–5.03; OR = 1.97, 95% CI: 1.14–3.43). Unhealthy mental states, such as anxiety and depression, and poor sleep quality led to high prevalence (OR = 3.16, 95%C I: 1.96–5.11; OR = 2.74, 95% CI: 1.76–4.26; OR = 2.14, 95% CI: 1.69–2.72, respectively). Conclusion Various types of FC prevail in China based on the different Rome criteria, personal characteristics, and habits. The prevalence also increased over the past three decades. The FC should be included under the primary care setting with uniform diagnosis criteria in China. Systematic Review Registration http://www.crd.york.ac.uk/PROSPERO, CRD42021277172.